The influence of brand image, brand ambassador, and content marketing on purchasing decisions on wardah lipstick exclusive matte lipcream products - Ilmiah, Elok Farikhatul; Kusumaningtyas, Dian (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim : The purpose of this study is to determine the influence of brand image, brand ambassador, and content marketing on the purchase decision of Wardah Lipstick Exclusive Matte Lipcream product Design/Methode/Approach : The model of approach used in this study is a quantitative causal approach, which is a research approach that seeks causal relationships between variables. The sampling technique uses simple random sampling of 40 respondents. The data analysis technique used is Assumption testklasik, regresi linear berganda, uji T (parsial), dan uji F (uji simultan). Research Finding : The results showed that the brand image variable partially did not have a significant effect on the purchase decision, while the brand ambassador and content marketing variables partially had a positive and significant influence on the purchase decision. However, simultaneously, these three variables had a positive and significant effect on purchase decisions with a contribution of 81.1%. Theoretical contribution/Originality : Research will be an additional experience and help the author to understand more deeply the theory obtained by comparing theoretical concepts with the realization in the field. This research can also be used as an additional reference in the field of management studies, especially marketing management and can be used as a reference for future research. Practitionel/Policy implication : The results of this study can be used by users of Wardah Lipstick Exclusive Matte Lipcream products to find out marketing strategies and consumer attraction. Research limitation : This research only focuses on three main variables, namely brand image, brand ambassador, and content marketing, as well as how they relate to consumer purchase decisions both partially and simultaneously. The researcher also limited the research respondents to all users of wardah lipstick exclusive matte lipcream.